Ru tailored hydrous cobalt phosphate as a rational approach for high-performance alkaline oxygen evolution reaction. (December 2022) - Shaikh, J.S.; Rittiruam, M.; Saelee, T.; Márquez, V.; Shaikh, N.S.; Santos, J.S.; Kanjanaboos, P.; Nazeeruddin, M.K.; Praserthdam, S.; Praserthdam, P.
Abstract: The water splitting is an appealing approach to fulfil the demand of energy without any global concerns. The oxygen evolution reaction is one of way to achieve unlimited energy from water but the low stability, high energy required to drive the reaction (overpotential), complicated and unscalable synthesis method of expensive catalysis restricts its real time implementation into modern society. Herein this report, we suggested Ru-tailored hydrous cobalt phosphate and its concentration effect as a dopant to improve the catalytic properties. Electrocatalytic properties were studied via linear sweep voltammetry, chrono-potentiometric studies at a 10 mA/cm 2 for 20 h, electrochemical active surface area, turnover frequency, and Tafel slope. Cobalt phosphate showed the connected-nanorods morphology, which is further tunned by increasing Ru-doping concentration, achieving various features from agglomerated nanorods sensitized with uniform nanoparticles on the micro-flower shapes consisting of interconnected nanorods sensitized with nanoparticles. The good electrocatalytic OER performance of 5% Ru-doped hydrous cobalt phosphate was achieved, exhibiting low overpotential up to 310 mV (vs. RHE) at 10 mA/cm 2 besides a small Tafel slope of 62 mV/dec in 1 M KOH. As well, stable O2 evolution for a period of 20 h was shown. DFT calculation reveals that the Ru can increase electrical conductivity and promote OER activity, observed from Bader charge analysis, electron density difference, and OER Gibbs free energy. The EIS plot, ECSA, and TOF estimation disclose that the increased electrical conductivity, the improved ECSA, and the high intrinsic activity are together responsible for the good OER activity for 5%Ru–CoPO. Graphical abstract: Image 1 Highlights: Ru-tailored hydrous cobalt phosphate for oxygen evolution reaction. 5% Ru doping achieved low overpotential 310 mV (vs. RHE) at 10 mA cm-2. Stable O2 evolution for a period of 20 h was shown. DFT calculation reveals how Ru enhanced OER activity.